The Role of Central Kalimantan Provincial Government in Improving Human Resource Quality through the One House One Graduate Program - Rakhdinda Dwi Arha Qairi; Sadar Sadar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2026)
This study aims to analyze the role of the Provincial Government of Central Kalimantan in improving human resource quality through the Satu Rumah Satu Sarjana (One House One Bachelor) Program as a strategic approach to family-based and socially inclusive educational development. Using a descriptive qualitative approach, the study relies on primary data obtained from in-depth interviews with key stakeholders and secondary data drawn from official government documents, statistical reports, and relevant publications. The findings indicate that the provincial government plays a strategic role in expanding access to higher education through regulatory support, scholarship provision, partnerships with universities, and mechanisms for identifying eligible households. The program has been shown to enhance educational motivation at the family level, strengthen the academic capacity of student beneficiaries, and generate broader social impacts in the form of increased educational aspirations among the younger generation. Nevertheless, the study also identifies several challenges, particularly the uneven distribution of information across regions and the limitations of program outreach. These issues highlight the need for more inclusive dissemination strategies and improved coordination among implementing institutions. Overall, the program contributes significantly to regional human resource development and serves as a replicable model of educational policy, provided that governance mechanisms and cross-sectoral collaboration are further strengthened.Recommendations are offered to enhance the program’s effectiveness, including improving evaluation systems, strengthening non-financial support for beneficiaries, and developing long-term planning related to graduate absorption and employment pathways